A comprehensive performance investigation of an under-floor air distribution system in the tropics / Poh Kai Sin - Poh, Kai Sin (2017)
Under-floor Air Distribution System (UFAD) is the technology that uses an under-floor plenum below a raised floor system to deliver conditioned air into the occupancy space for human comfort in a commercial building. A well-engineered UFAD system can provide the flexibility of restructuring the layout of the interior space, reduce energy consumption, and improve thermal comfort, ventilation efficiency and indoor air quality as compared to the overhead air distribution (OHAD) system. However, the research and technical data on the application of UFAD system in the tropics is very limited. Hence, the application of the UFAD system for human comfort in the tropics is not widely known. This study is divided into three sections to investigate the performance and the application of UFAD system for human comfort, and the integration of a solar photovoltaic (PV) system into the UFAD system in the tropics. First, the fieldwork measurement was conducted to study the thermal environmental and indoor air quality of an existing UFAD system in a high-rise office building in Malaysia. It was found that the air stagnation at the occupancy space is critical as all the air velocities measured at the locations according to the Industry Code of Practice on Indoor Air Quality were well-below the minimum required air velocity of 0.15 m/s. The average air velocities measured are in the range of 0.04 – 0.06 m/s. The airflow pattern of the swirl floor diffuser was then tested at an airflow testing laboratory. Computational Fluid Dynamics (CFD) was used to extend the study on the swirl floor diffuser to various grille designs, diffuser blades and airflow rates to investigate the diffuser’s performance according to ASHRAE standard. Finally, the energy consumption of the air-handling unit (AHU) for the UFAD system has been analyzed with the integration of a solar PV system in the tropics. The findings of this study show that the diffuser’s design and selection, HVAC system design, construction, operation and maintenance are equally important to produce a UFAD system that achieves significant advantages over the OHAD system.